Enhanced Big Data Platform for Visualization of Employee Data. - Manishankar S; S. Sathayanarayana (JOIV : International Journal on Informatics Visualization, 2018)
In this Digital world storage area capacity required for an Enterprise is quite huge, and processing that Big Data is one of the major challenging areas in todayâ€™s information technology. As the heterogeneous data from the various sources grow rapidly, there should be some proficient way for data storage for each enterprise. Most of the Enterprises have a tendency to migrate their data in to servers with high processing capability to handle variety and voluminous data. Major problem that arises in such big data servers of an Enterprise is the process involved in segregating data according to their types. In this research, an efficient methodology is proposed which handles the segregation of data inside a server with multi valued distribution-based clustering. These clustering-based solutions provide an efficient visualization of varying data in the server and also a separate visualization of employee data too. The paper discusses about the simulation of the clustering technique with respect to an Enterprise data and visualization of file storage structure and categorization of data, also it gives a picture of performance of the Big data server.Â